Association of young age and male sex with primary sclerosing cholangitis in Taiwanese patients with inflammatory bowel disease - Meng-Tzu Weng; I-Lun Shih; Chien-Chih Tung; Yew-Loong Leong; Ming-Jium Shieh; Cheng-Yi Wang; Jau-Min Wong; Yen-Hsuan Ni; Shu-Chen Wei (Intestinal Research, 2022)
Background/Aims Primary sclerosing cholangitis (PSC) is associated with inflammatory bowel disease (IBD). We aimed to evaluate the prevalence, clinical manifestation, and outcomes of PSC in Taiwanese patients with IBD. Methods This retrospective study enrolled patients with IBD admitted from January 1, 1996, to December 31, 2018, to National Taiwan University Hospital. A case-matched analysis was performed comparing patients with IBD with and without PSC according to age, sex, and time of admission, with ratios of 1:4 and 1:2 in the adult and pediatric groups, respectively. Results In total, 763 patients with IBD were enrolled, 12 of whom were also diagnosed with PSC (1.57%). All these patients had ulcerative colitis (UC). A greater incidence of IBD with PSC was observed in younger patients than in older patients. Male sex was a risk factor for PSC in pediatric patients with IBD (P=0.015); 75% of these patients were diagnosed with PSC along with or after the diagnosis of UC. There was no significant difference in colitis extent and severity between the groups; however, a higher proportion of rectal sparing was observed in patients with PSC (P=0.001). There was no significant difference in cancer development between the groups (P=0.679). Conclusions A 1.57% prevalence of PSC was observed in Taiwanese patients with IBD. The majority of patients with IBD and PSC were men and were diagnosed at a younger age. Hence, routine evaluation of biliary enzymes and liver imaging is recommended in young male patients with IBD.